Population structure and ecology of Aloe lettyae, an endangered Woodbush Granite Grassland endemic - Kremer-Kohne, Sylvie (My University, 2018)
This is the first study on the biogeography, population biology and reproductive ecology of the endangered Aloe lettyae endemic to the highly threatened Woodbush Granite Grassland (WGG) in Limpopo Province, South Africa. A. lettyae's distribution has been severely reduced by habitat loss and fragmentation and most populations were clustered on the south western side of the WGG polygon, with all known localities less than 40 km apart in this fragmented vegetation type. In total, 19 A. lettyae populations were located and documented, and the total area of occupancy was calculated ( 17 .5 ha). Population size varied from 10 to 4000 plants, with 8500 individuals estimated in total, and plants occurred in clumps. Plant size and stage demographics were determined in seven of the 19 currently known A. lettyae populations which included the two largest populations with ~4000 and ~3000 A. lettyae plants, respectively, as well as a high- and a low-lying population, and constituted a representative sample over the entire geographical range of A. lettyae. Based on number of leaf layers and leaf rosette diameter, across all surveyed populations, 15% of the plants were juveniles, 9% were subadults, 15% non-reproductive adults and 61 % reproductive adults. There was a clear difference in population structure between the main population and the second largest population, with the main population having a higher proportion of juveniles (14%) than the second largest population (3% ). The low percentages of juveniles and non-reproductive subadults indicated an apparent current and historic lack of recruitment. Most size class distributions (SCDs) (76%) were bell-shaped which included the two largest populations, 9% were J-shaped, 3% had an inverse J-shaped SCD and 12% had an irregular SCD. Aloe lettyae grows in tall, dense grassland vegetation. For all surveyed populations combined, habitat profile within 1 m of an A. lettyae individual and 2: 5 m away from A. lettyae plants in adjacent non-populated areas varied very little, but habitat variables differed significantly between populations. Percentages aerial covers for grass, forbs and woody species were 50%, 37% and 5% for the largest population and 49%, 26% and 15% for the second largest population with the small remaining percentages being made up of bare soil and rock cover. The main threats to A. lettyae were identified as misapplication of fire, cattle grazing and invasive alien plants.In the A. lettyae populations surveyed in 2016/7, approximately 80% of the adult individuals were reproductive. Reproductive success in terms of fruit set and seed production was monitored in the two largest A. lettyae populations with -3000 plants each and four smaller populations with <350 plants each. Fruit set varied from 29% in the largest population to 3% in the smallest population. Total seed production per plant was high in the large populations (5200 and 2400), compared with the four smaller populations surveyed (130-920), which indicated that an Allee effect may be operating. Approximately 90% of the sampled intact fruit contained seed predators, a fly (Apenthecia cf. crassiseta, Drosophilidae) and/or a wasp (Eurytoma sp., Eurytomidae). During flowering, camera traps were used at four localities to identify the main floral visitors, bird visitation and probe rates. Three bird species were observed feeding on A. lettyae nectar, Amethyst sunbirds (Chalcomitra amethystina) as well as Southern and Greater Double-collared sunbirds (Cinnyris chalybeus and Cinnyris afer). Amethyst sunbirds, the most frequent visitors (554 visits/1000 plants/h), were observed at all four localities monitored, while Double-collared sunbirds only occurred at two localities and had a much lower visitation rate (46 visits/1000 plants/h). Aloe lettyae nectar volume in unscreened flowers was very variable (range 5-85 µI; mean 15.5 ± 1.2 µI) and nectar sugar concentration was high (range 11-25%; mean 18.6 ± 0.2%) confirming that A. lettyae flowers are adapted for specialist nectarivores. The contribution of different pollinator guilds (birds and insects) was determined through selective pollinator exclusion treatments which showed that birds contributed significantly more to A. lettyae fruit set (1.7 times), seed production per fruit (1.5 times) and seed production per plant (4.3 times) than insects. In a germination trial conducted under controlled conditions with seeds from the populations monitored for their reproductive success and seeds obtained from the pollinator exclusion trial, mean germination time was approximately 2.5 weeks· and cumulative germination rates were high (approximately 90% ), and did not differ between populations/treatments. In combination with baseline A. lettyae population data provided by this study, the understanding of A. lettyae 's reproductive ecology will aid in designing an adaptive grassland management strategy. The history of habitat loss and fragmentation, coupled with the severe reproductive decline as A. lettyae population size declines (Allee effect), points to the necessity to conserve the remaining small extent of WGG.
A dissertation presented in fulfillment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, 2018